Hemichrome Determination by Thermal Lensing with Polyethylene Glycols for Signal Enhancement in Aqueous Solutions. (24th July 2018) - Galimova, Viktoriya R.; Liu, Mingqiang; Franko, Mladen; Volkov, Dmitry S.; Hibara, Akihide; Proskurnin, Mikhail A.
ABSTRACT: The thermal lens technique is proposed for the determination of total hemoglobin in the form of reversible hemichrome. The conditions were optimized (concentration of sodium dodecyl sulfate, 2 mM) to attain the maximum sensitivity with the use of polyethylene glycols as signal enhancers. For polyethylene glycols with molecular weights 1500–35000 Da in a concentration range of 5–15% w/w (5–25 mM), the influence on thermal lens signal enhancement was estimated. It is shown that the use of 5% w/w polyethylene glycol 2000 provides the maximum increase in the thermal lens enhancement factor (by 40%) in comparison with unmodified aqueous solutions. The detection limit of iron(II) tris (1, 10-phenanthrolinate) as a model system is 60 nM. Under these conditions, the thermal lens detection limit of hemichrome is 10 nM, which shows a 15-fold enhancement compared to spectrophotometry. Modification of the medium with polyethylene glycols decreases the limit of detection of hemichrome determination by 15% in comparison with unmodified aqueous solutions due to better reproducibility for the range of concentrations from 0.02 to 0.9 µM.